NIR fluorescence for monitoring in vivo scaffold degradation along with stem cell tracking in bone tissue engineering - Kim, Soon Hee; Park, Ji Hoon; Kwon, Jin Seon; Cho, Jae Gu; Park, Kate G.; Park, Chan Hum; Yoo, James J.; Atala, Anthony; Choi, Hak Soo; Kim, Moon Suk; Lee, Sang Jin (Biomaterials, 2020)
Stem cell-based tissue engineering has the potential to use as an alternative for autologous tissue grafts; however, the contribution of the scaffold degradation along with the transplanted stem cells to in vivo tissue regeneration remains poorly understood. Near-infrared (NIR) fluorescence imaging has great potential to monitor implants while avoiding autofluorescence from the adjacent host tissue. To utilize NIR imaging for in vivo monitoring of scaffold degradation and cell tracking, we synthesized 800-nm emitting NIR-conjugated PCL-ran-PLLA-ran-PGA (ZW-PCLG) copolymers with three different degradation rates and labeled 700-nm emitting lipophilic pentamethine (CTNF127) on the human placental stem cells (CT-PSCs). The 3D bioprinted hybrid constructs containing the CT-PSC-laden hydrogel together with the ZW-PCLG scaffolds demonstrate that NIR fluorescent imaging enables tracking of in vivo scaffold degradation and stem cell fate for bone regeneration in a rat calvarial bone defect model. This NIR-based monitoring system can be effectively utilized to study cell-based tissue engineering applications.
Keywords: Autologous tissue; Bone regeneration; Bone tissue engineering; Fluorescent imaging; Hybrid constructs; Near infrared (NIR) fluorescence imaging; Scaffold degradation; Tissue engineering applications; Animals; Bone Regeneration; Cell Tracking; Female; Hydrogels; Pregnancy; Rats; Stem Cells; Tissue Engineering; Tissue Scaffolds; Biodegradation; Imaging; NIR fluorescence; Scaffold; Stem cells; Tissue engineering